Elements in movie trailers that motivates audience to watch movies in Malaysia: a quantitative approach - Abu Bakar, Mohd Syuhaidi; Bolong, Jusang; Bidin, Rosmiza; Ayub, Nur Syuhaidah; Jono, Siti Nor Fazira; Mat Shuki, Mohamad Syafiq (Asian Scholars Network, 2020)
Movie trailers are known as tools for selling a movie. The success of a movie is largely attributed to a good trailer presentation. What makes a good movie trailer? What elements are needed to make a good trailer? This paper uncovers the necessary elements of a movie trailer needed to motivate audiences to watch a movie in Malaysia. This quantitative study constructed a survey of elements of movie trailers found in the literature. Google Form was distributed to 250 respondents, purposively selected for this stud and data were analyzed using descriptive analysis. The data collected in this study found 7 elements in trailers that have influenced audiences to watch movies in Malaysia, which are – Color, Storylines, scene sequence, three-act structure, director or the production company, cast (actors and actresses); and cinematography. The data obtained can help filmmakers and film marketers in Malaysia to see what element movie trailers can be utilized to help increase their movie sales.